Multicultural academic experience and multicultural counselling competency in addressing polygamous family structures among registered counsellors in Malaysia - Chen Siew Kee, Rose; Manouchehri, Mahshid; Hanafi, Norshafizah; Hassan, Siti Aishah (Universiti Putra Malaysia, 2024)
To effectively conduct counselling sessions, professional counsellors in Malaysia need to possess multicultural competence, especially considering the discrepancies between the ideal and the actual understanding of polygamous marriages. Thisstudy examinesthe relationship between multicultural academic experience, multicultural counselling competency, and the competency of counsellorsin addressing polygamousfamily structures among 370 registered counsellorsin Malaysia.The collected data was analysed using PearsonCorrelations, One-Way ANOVA and Multiple Regressions. The findings indicate that the respondents demonstrated high multicultural academic experience and multicultural counselling competency. There was a significant positive correlation betweenmulticultural academic experience andmulticultural counselling competency, as well as the competency of counsellors in handling polygamous families. Moreover, there were noteworthy variationsin competency levels based on ethnicity. This study highlights the crucial role of multicultural academic experience and multicultural counselling competency in predicting the competency of counsellors when dealing with polygamous families. Futher validation of the Counselor' Multicultural. Competency on the Polygamous Family Structure Scale is recommended in future studies encompassing larger and more diverse populations.